Monitoring the reliability of integrated circuits protection against Trojans: encoding and decoding of combinational structures - L. A. Zolotorevich; V. A. Ilyinkov (Informatika)
Integrated circuits, systems on a chip are the key links in various industrial systems and state defense systems. The emergence of counterfeit integrated circuits, problems of piracy, overproduction, unauthorized interference in the design of microcircuit, hardware Trojans require the development of methods and means of their timely detection. Trojans can be introduced into the integrated circuits structure both on the development stage and during the production process, including the stages of specification, design, verification and manufacturing. The inclusion of additional elements in the integrated circuits structure jeopardizes the functional suitability and reliability of the system as a whole. For the purpose of hardware protection of projects, the methods of hardware coding are currently used.The paper discusses the features and reliability of logical coding of combinational circuits. An algorithm for cracking the code of combinational circuits is proposed, based on the description of encoded structure by the resolution function and reducing the problem to SAT CNF. The initial data for decoding the structure of a digital device is the structural implementation of encoded circuit, obtained, for example, by reverse engineering (prototype design), as well as an activated physical sample of an integrated circuit, when into protected from unauthorized access memory the correct key value is loaded. This sample can be used as a black box model. The main idea of breaking a key is to solve a problem without research on a large interval of values of input and output variables.